Pemanfaatan Media Puzzle In-Group Untuk Pembentukan Karakter Kerjasama Anak: Di RA Al-Hidayah UIN Walisongo - Asfarina, Nihayatu; Filasofa, Lilif Muallifatul Khorida (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2025)
The purpose of this study is to determine the formation of children's characters to cooperate through in-group puzzle games. This research is based on the fact that children at RA Al-Hidayah UIN Walisongo lack cooperation, especially those in class A. Early childhood has the ability to think critically and their imagination is very large, and they have strong cooperation skills. Therefore, these skills must be stimulated as early as possible so that they become assets for children when they grow up. This case study-based descriptive qualitative research describes a research project. Data were collected by observation, interviews and documentation. The results of this study show that puzzle media can shape the character of children's cooperation in RA Al-Hidayah. In this case, it can be seen from the improved communication relationships between children, the more effective division of roles, and their ability to solve puzzles faster. Collaboration skills are very important for early childhood because they can have a positive impact on their growth and development.